Influence of audience behavior on collegiate football players - Togores, Orlan Joseph C. 1999-
This research is conducted to examine the influence of audience behavior on collegiate football players’ psychological states. There have been a few studies carried out to examine the influence of audience behavior on athletic performance, but little is known about the insights of the players whether they find the behavior of the audience (e.g. cheering and jeering) facilitative or debilitative. Cheering can be attributed to a supportive audience which positively influences the performance of football players. In contrast, jeering from an unsupportive audience negatively influences performance. This study focuses on how audience behaviors in UAAP men’s football influences the player’s performance in the game. A purposeful sample consisting of 6 men’s collegiate football players participated in individual semi-structured interviews. The study employed a qualitative approach using thematic analysis to investigate the influence of audience behavior on the psychological states of collegiate football players. Results show that participants are influenced by both the presence of audience and their behaviors but the influence varies depending on the participants’ individual perceptions and experiences throughout the duration of the games. Results of this research call for more in-depth psychological interrogations and interventions to gain more understanding on the influence of audience behavior for future research